Circulating levels of growth hormone in postural orthostatic tachycardia syndrome - Madeleine Johansson (Nature Portfolio, 2021)
Abstract Postural orthostatic tachycardia syndrome (POTS) is a cardiovascular autonomic disorder with poorly understood etiology and underlying pathophysiology. Since cardiovascular morbidity has been linked to growth hormone (GH), we studied GH levels in patients with POTS. We conducted an age-sex-matched case–control study in patients with POTS (age 31 ± 9 years; n = 42) and healthy controls (32 ± 9 years; n = 46). Plasma GH levels were measured using high-sensitivity chemiluminescence sandwich immunoassay. The burden of orthostatic intolerance symptoms was assessed by the Orthostatic Hypotension Questionnaire (OHQ), consisting of a symptom assessment scale (OHSA) and a daily activity scale (OHDAS). POTS patients had significantly higher composite OHQ score than controls, more symptoms and less activity. Supine heart rate and diastolic blood pressure (BP), but not systolic BP, were significantly higher in POTS. Median plasma GH levels were significantly lower in POTS (0.53 ng/mL) than controls (2.33 ng/mL, p = 0.04). GH levels were inversely related to OHDAS in POTS and supine systolic BP in POTS and controls, but not heart rate neither group. POTS is associated with lower GH levels. Impairment of daily life activities is inversely related with GH in POTS. A higher supine diastolic BP is inversely associated with GH levels in POTS and healthy individuals.